Prognostic impact of visceral and subcutaneous fat area in stage I-III colon cancer patients with cachexia: a population-based multicenter study - Liang, Xian-wen; Wen, Jing; Liu, Bing; Wang, Sheng-zhong; Wu, Jin-cai; Pan, Tao (Frontiers in Nutrition, 2025)
BackgroundAdipose tissue reduction is one of the features in patients with cancer cachexia. However, it remains unclear whether visceral fat area (VFA) and subcutaneous fat area (SFA) contribute differently to the progression of cancer cachexia in colon cancer patients. This study aims to investigate the prognostic impact of VFA and SFA in stage I-III colon cancer patients with cachexia.MethodsPatients diagnosed with stage I-III colon cancer were preoperatively measured for VFA and SFA and then divided into VFA-high (VFA-H) and VFA-low (VFA-L) groups, as well as SFA-high (SFA-H) and SFA-low (SFA-L) groups. The prognostic impact of VFA and SFA for colon cancer patients with cachexia were analyzed using the Kaplan–Meier method and Cox regression analysis.ResultsA total of 916 colon cancer patients (377 with cachexia and 539 without) were included in the study. In patients with cachexia, the estimated five-year overall survival (OS) was higher in the VFA-H group compared to the VFA-L group (p < 0.001). There was no significant difference in five-year OS between the SFA-L and SFA-H groups (p = 0.076). Cox regression analysis indicated that VFA (hazard ratio [HR] = 0.55, 95% confidence interval [CI] 0.40 to 0.76; p < 0.001) was an independent prognostic factor for patients with cachexia. SFA (HR = 0.78, 95% CI 0.59 to 1.03; p = 0.076) was not an independent prognostic factor for patients with cachexia.ConclusionPreoperative VFA, but not SFA was a useful prognostic factor for long-term outcomes in stage I-III colon cancer patients with cachexia. More attention should be paid to VFA in colon cancer patients with cachexia.